USE OF DIGITAL TECHNOLOGIES IN CHILDREN'S SPEECH AND LANGUAGE CORRECTION WORK IN PRESCHOOL - Vindece, Aija; Usca, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In today's society, a child lives in a technology environment since birth, and it changes children's perception and learning habits, determining the necessity to use digital technologies that are interesting for preschool children, motivates them to perform speech and language corrective actions consciously, and enables the development of self-control of speech.The objective of the paper is to stimulate discussion on the possibilities of using digital technologies in the correction of children's speech and language in preschool, based on the analysis of theoretical literature and the availability of means used in speech therapy correction.Methods - literature analysis, survey of practicing speech therapists.The results suggest that choice of means is determined by speech therapists' personal attitude toward digital technologies, which is influenced by respondents' experience and availability of technologies within the educational institution.